OPTIMASI LP (LOW PRESSURE) AUXILIARY STEAM PADA DESALINATION PLANT UNTUK MENINGKATKAN PRODUKSI STEAM TURBINE PLTGU GRATI - Deni Prasetio; Muhammad Agus Sahbana; Dadang Hermawan (Prodi Teknik Mesin Universitas Yudharta, 2021)
Desalination Plant, which is an equipment that functions to distill sea water into fresh water by a heating process. The operation of the desalination plant in the generating system affects the production results produced by the steam turbine. The steam used is HP (High Pressure) Auxiliary steam on the ejector which functions to make the chamber a vacuum, and LP (Low Pressure) Auxiliary steam on the brine heater which functions to heat sea water. The use of HP (High Pressure) Auxiliary steam at the ejector causes a greater reduction in electricity production in the steam turbine when compared to the use of LP (Low Pressure) Auxiliary steam. This causes the cost to produce distillate to be more expensive and the production of electricity generated in the steam turbine is not optimal. Currently, the operation of the desalination plant of the Grati PLTGU is still using HP (High Pressure) Auxiliary steam to make the desalination plant chamber into a vacuum condition. The innovation is to replace the use of HP (High Pressure) Auxiliary steam with LP (Low Pressure) Auxiliary steam at the ejector desalination plant, with the aim of reducing distillate costs and increasing the optimization of electricity production generated by the steam turbine. The use of LP (Low Pressure) Auxiliary steam on the ejector is proven that the distillate value, condensate value and load setter are in normal conditions and the performance of the desalination plant is maintained. steam turbine of 26,761 kWh